2017
DOI: 10.1002/jcc.24763
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of solid‐state 43Ca NMR parameters: A comparison of periodic and cluster approaches and an evaluation of DFT functionals

Abstract: We present a computational study of magnetic-shielding and quadrupolar-coupling tensors of Ca sites in crystalline solids. A comparison between periodic and cluster-based approaches for modeling solid-state interactions demonstrates that cluster-based approaches are suitable for predicting Ca NMR parameters. Several model chemistries, including Hartree-Fock theory and 17 DFT approximations (SVWN, CA-PZ, PBE, PBE0, PW91, B3PW91, rPBE, PBEsol, WC, PKZB, BMK, M06-L, M06, M06-2X, M06-HF, TPSS, and TPSSh), are eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Our previous computational study based on various model chemistries and more than 10 calcium‐containing crystals indicated that 43 Ca chemical‐shift and quadrupolar‐coupling calculations at the HF/cc‐pVTZ level probably offer the maximum benefits in terms of computational accuracy and computing time and resources . The 43 Ca chemical‐shift calculation at the HF/cc‐pVTZ level, based on a cluster model derived from the X‐ray single crystal structure of ATC‐EG with optimized hydrogen positions, agrees reasonably well with the experimental results (Table ).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Our previous computational study based on various model chemistries and more than 10 calcium‐containing crystals indicated that 43 Ca chemical‐shift and quadrupolar‐coupling calculations at the HF/cc‐pVTZ level probably offer the maximum benefits in terms of computational accuracy and computing time and resources . The 43 Ca chemical‐shift calculation at the HF/cc‐pVTZ level, based on a cluster model derived from the X‐ray single crystal structure of ATC‐EG with optimized hydrogen positions, agrees reasonably well with the experimental results (Table ).…”
Section: Resultssupporting
confidence: 72%
“…Calculated 13 C magnetic‐shielding parameters were converted to the chemical‐shift scale using a referencing scheme summarized by Sefzik, Fidler, Iuliucci, and Facelli . Calculated 43 Ca shielding constants were converted to chemical‐shift values according to a computational survey of calcium‐containing materials . Euler angles were extracted from the Gaussian 09 output files using the program EFGShield …”
Section: Sample Preparation and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This functional has been widely used for the calculation of magnetic properties in organic, inorganic and solid compounds, providing results comparable with experiments. 38,[54][55][56] Vibrational frequency calculations were performed at the same level to effectively obtain a true-minimum on the potential energy surface (PES), with the exception of the planar COT, which has one imaginary frequency (156.1i cm…”
Section: Computational Detailsmentioning
confidence: 99%